Facts About Folate - Linda B Bobroff (EDIS)
Everyone needs folate. It is especially important for women who can become pregnant. Pregnant and nursing women, growing children, and older adults also need plenty of folate. This 2-page fact sheet is a major revision that discusses folate requirements, ways to meet those requirements, and possible effects of folate deficiency. Written by Linda B. Bobroff, and published by the UF/IFAS Department of Family, Youth and Community Sciences, revised February 2018. http://edis.ifas.ufl.edu/fy186